LINGUISTIC ARCHAISMS AND LEGAL ANACHRONISMS IN THE CONSTITUTION OF THE KINGDOM OF DENMARK - JAROSZ, Józef (Comparative Legilinguistics, 2010)
The present paper analyzes the constitution of the Kingdom of Denmark, the contents and linguistic form of which are based to a large extent on the first Danish fundamental statute of 1849. The study takes two directions: along with notes on the constitution‘s language, the factual contents of the text is assessed. Conclusions are examined with reference to both the function of the text from a linguistic perspective and the function of the constitution in the context of the function of law. The study in the linguistic sphere indicates a number of lexical archaisms, syntactical complexities and stylistic imperfections which seriously restrict comprehension of the constitutional text. Analysis of contents shows that the text refers more than once to non-existent legal status and historical realities, while sociopolitical changes occurring since the last amendments in 1953 are not reflected and it therefore fails to include the values essential to a contemporary society. These shortcomings of the Danish constitution are direct reasons why some functions attributed to the fundamental statute are weaker. Awareness of this fact became a direct impulse for Danish members of parliament to initiate a nation-wide debate over revising and supplementing the contents of the constitution in order to restore its desirable functions in a democratic country.